2008
DOI: 10.1159/000124286
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Long-Term Efficacy of Subcutaneous and Sublingual Immunotherapies in Perennial Rhinitis

Abstract: Background: Both sublingual and subcutaneous immunotherapies have a documented clinical efficacy, but only a few comparative studies have been performed. Objectives: To evaluate and compare the long-term efficacies of subcutaneous and sublingual immunotherapy. Methods: One hundred and ninety-three patients with house dust mite allergies, out of an original total of 230, were treated with subcutaneous and sublingual house dust mite-specific immunotherapies for 3 years and also observed for 3 years after discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…These studies were published from 1993 to 2011, with dust mite the most common allergen studied (60 %). The studies all have small number of subjects with the exception of Tahamiler et al [38]. While the majority of these studies find both SLIT and SCIT efficacious, there is no clear agreement among the studies as to which form of treatment is more effective.…”
Section: Efficacy Of Slit Versus Scitmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were published from 1993 to 2011, with dust mite the most common allergen studied (60 %). The studies all have small number of subjects with the exception of Tahamiler et al [38]. While the majority of these studies find both SLIT and SCIT efficacious, there is no clear agreement among the studies as to which form of treatment is more effective.…”
Section: Efficacy Of Slit Versus Scitmentioning
confidence: 99%
“…Several published prospective studies have compared the efficacy of sublingual to subcutaneous immunotherapy [32][33][34][35][36][37][38][39][40][41], and these are detailed in Table 1: Prospective Studies of SLIT versus SCIT. These studies were published from 1993 to 2011, with dust mite the most common allergen studied (60 %).…”
Section: Efficacy Of Slit Versus Scitmentioning
confidence: 99%
“…The comparative effectiveness of SLIT to SCIT continues to be a topic of great interest. Prospective studies of SLIT have not found clear agreement as to which form of treatment is more effective . A recent systematic review of head‐to‐head studies of SLIT and SCIT found low‐grade to moderate‐grade evidence supporting that SCIT is more effective for allergic asthma and allergic rhinoconjunctivitis, but the authors cautioned that more studies are required to strengthen the evidence base …”
Section: Comparison Of Slit and Scitmentioning
confidence: 99%
“…One study of perennial allergic rhinitis concluded that over a 6-year follow-up period, those treated with subcutaneous therapy fared better than those treated with SLIT in regard to symptom scores, skin prick testing, and nasal allergen challenge scores. They concluded that the sublingual route should be offered as an alternative second-line treatment for those who refuse subcutaneous therapy [35]. Others suggest that SLIT provides notable improvements in symptoms [36,37•], improves quality of life [38], and reduces medication use in adults and children [37•,39]; thus, they argue that it is a revolutionary addition to immunotherapy.…”
Section: Sublingual Immunotherapymentioning
confidence: 99%